2022
DOI: 10.37934/cfdl.14.1.6686
|View full text |Cite
|
Sign up to set email alerts
|

Stability Solution of Unsteady Stagnation-Point Flow and Heat Transfer over a Stretching/Shrinking Sheet in Nanofluid with Slip Velocity Effect

Abstract: Computational of unsteady flow with slip condition is essential since physically the heat transfer process is time-dependent and there may exist slip between fluid and surface. Therefore, this study aims to investigate the unsteady stagnation-point flow and heat transfer over a stretching/shrinking sheet immersed in nanofluid in the presence of slip velocity. By applying boundary layer theory and Tiwari-Das model, the governing equations are developed and transformed into a system of ordinary differential equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The two-dimensional flow across an exponentially stretched surface was studied by Magyari and Keller [9], and Elbashbeshy [10] followed up with a similar investigation which considered the mass suction on the exponentially surface. More recent studies of nanofluid at various physical parameters can be seen in the existing literature [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The two-dimensional flow across an exponentially stretched surface was studied by Magyari and Keller [9], and Elbashbeshy [10] followed up with a similar investigation which considered the mass suction on the exponentially surface. More recent studies of nanofluid at various physical parameters can be seen in the existing literature [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The heat transmission of nanofluids in a cavity composed of a vertical porous layer is analyzed by Al-Zamily [32]. Fadhilah et al [33] studied the heat transfer and stagnation point flow in an unstable nanofluid across a porous surface that is exponentially stretching and decreasing. Mehryan et al [34] demonstrated an increase in heat transfer in hybrid nanofluids flowing through porous surfaces under the influence of magnetic fields and convection.…”
Section: Introductionmentioning
confidence: 99%